The Link Class Project: Collaborative virtual teams between Peru and The Netherlands - Olivos Rossini, Mariella (2015)
The Link Class Project presented in this article provides an example of established collaborative group activities to negotiate and build a report together in virtual teams composed of students at Universidad ESAN Lima (Peru) and Tilburg University Tilburg (Netherlands). It further analyzes the effects of a campus based internationalization strategy supported by the use of technology. Based on previous experiences with virtual classrooms the authors adhere to the ancient Chinese philosopher’s Lao Tzu quote: «If you tell me I will listen; if you show me I will see; but if you let me experience I will learn».